Hubungan Pengetahuan Ibu Tentang Food Borne Diseases, Water Borne Diseases dan Pengelolaan Sampah Dengan Kejadian Diare Pada Balita - Sarifatul Asmah; Ade Dita Puteri; Nila Kusumawati (Media Kesehatan Politeknik Kesehatan Makassar, 2024)
Diarrhea is a condition of increased frequency of defecation more than 3 times in 24 hours with loose stools. The purpose of this study was to determine the relationship between mother knowledge about food borne diseases, water borne diseases and waste management with the incidence of diarrhea in toddlers in the Air Tiris Community Health Center work area. Using a quantitative analytical design with a crosssectional approach. The number of samples was 97 respondents with a questionnaire measuring instrument that had been tested for validity and reliability. Statistical tests used chi square. The results showed that mothers who had good knowledge about food borne diseases were 76.3%, mothers who had good knowledge about water borne diseases were 75.3%, mothers who did poor waste management were 53.6% and toddlers who experienced diarrhea were 54.6%. Statistical tests showed that there was no significant relationship between maternal knowledge about food borne diseases, water borne diseases with the incidence of diarrhea in toddlers by values ​​p=.655 and p=.259 (p> 0.05). While there was a significant relationship between waste management with the incidence of diarrhea in toddlers indicated by a value of p = 0.013 (p <0.05). Suggestions to related agencies to carry out education regarding good waste management so that diarrheal incidents in toddlers can be prevented in the future.  Keywords : Food borne diseases; water borne diseases; waste; diarrrhea